Enhancing Microstructure, Grain Refinement, and Wear Properties of Cast A356-TiB2 Composite through Improved Sequence of ECAP and Heat Treatment Processes - Seman, Anasyida; Syukron, Muhammad; Hussain, Zuhailawati; Hassan, Muhammad Hafiz; Dhindaw, Brij Kumar; Abioye, Taiwo Ebenezer; Zakaria, Siti Aminah (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
This study aimed to enhance the grain structure, hardness, and wear resistance of A356-1.5TiB2 composite through a combination of manufacturing processes. Initially, the composite was produced using casting, followed by equal channel angular pressing (ECAP) and heat treatments in various sequences. The heat treatment process involved a solution heat treatment (540ºC, 4 hours), followed by rapid quenching in water (90ºC). The ECAP process was carried out via the BA route, involving four passes at room temperature. After ECAP, an aging process was conducted at 155ºC for 3 hours. The post-application of ECAP and heat treatments had a positive impact on the distribution of TiB2 and TiAl3 particles, aluminum matrix grain refinement, and improved hardness and wear properties of the composite. The composite underwent both ECAP and heat treatment exhibited finer grain structure and higher hardness. The sequence of post-applications of ECAP and heat treatments also affected the grain structure, hardness, and wear resistance of the composite. The composite that underwent solution treatment followed by aging treatment and then ECAP demonstrated the most refined structure and highest hardness. These findings demonstrate that a carefully designed manufacturing process can significantly enhance the mechanical properties of A356-1.5TiB2 composite.